A Review on the Effect of Mechanical and Thermal Treatment Techniques on Shape Memory Alloys - Mohammed, Safar Saeed; Kök, Mediha; Qader, Ibrahim; Qadır, Razaw (Niyazi BULUT, 2022)
Despite of many interesting behaviors and attractive properties of Shape memory alloys (SMAs), there are some drawbacks and limitations that prevent them from being used in technology. But there are some treatment techniques that can be used to improve the behaviors of shape memory alloys. Also, they can remove or reduce the limitations of SMAs. In this study both and mechanical treatment techniques (Ball- and Roller-Burnishing Treatment, Surface mechanical attrition treatment, and Laser shock peening) and heat treatment techniques (Annealing, Normalizing, Hardening, and Tempering) have been clarified. And the effect of both treatment techniques of the properties of shape memory alloys have been reviewed.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri